Greenwashing and Promotion: Their Influence on Le Minerale Repurchase Intention - Alviani Tri Wulandari; Kurniawati Darmaningrum; Darsono (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: The main object tive of this study is to examine the influence of greenwashing perception and promotion on repurchase intention packaged drinking water products of Le Minerale. Methodology: The methodology used is a quantitative approach. The study was conducted with 133 respondents who had purchased Le Minerale. Data analysis techniques used in this study include instrument testing, classical assumption testing, hypothesis testing using partial tests (t-test), simultaneous tests (f-test), coefficient of determination and multiple linear regression analysis using the SPSS Statistics version 27 application. Main Findings: The results of the tests carried out in this study show that the perception of greenwashing and promotions has a positive and significant influence on the decision to repurchase intention packaged drinking water products () of Le Minerale. Novelty/Originality of this study: This study breaks new ground by specifically examining the influence of greenwashing perception and promotion on repurchase intention packaged drinking water products () market, focusing exclusively on the Le Minerale brand. While previous studies have explored greenwashing and repurchase intention separately or in a broader context, this study uniquely synthesizes these elements within a specific market dynamic in Indonesia and for a leading brand and offers new insights for academic understanding and marketing strategies in this significant product category.